Composite of cellulose and inorganic porous coordination polymer, and method for producing same

By synthesizing inorganic PCPs inside the cellulose structure, the method addresses the challenges of PCP detachment and strength reduction, resulting in a stable, high-loading composite with versatile applications.

JP7648081B2Active Publication Date: 2025-03-18ASAHI KASEI KOGYO KABUSHIKI KAISHA +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021010929
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-28
Filing Date
2021-01-27
Publication Date
2025-03-18
Estimated Expiration
2041-01-27

AI Technical Summary

Technical Problem

Existing methods for creating composites of inorganic porous coordination polymers (PCPs) with cellulose face challenges such as easy detachment of PCPs, damage to PCP pores, and limited ability to carry a large amount of PCP without reducing the strength of the composite.

Method used

The method involves dissolving cellulose in a solvent containing metal ions and reacting with a ligand solution to synthesize inorganic PCPs inside the cellulose structure, resulting in a composite with a high loading ratio of PCPs that is difficult to desorb and maintains strength.

Benefits of technology

This approach allows for the creation of a composite with a high loading ratio of inorganic PCPs that is stable, easy to handle, and can be shaped arbitrarily for various applications, including storage, separation, and electronic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648081000007
    Figure 0007648081000007
  • Figure 0007648081000008
    Figure 0007648081000008
  • Figure 0007648081000009
    Figure 0007648081000009
Patent Text Reader

Abstract

To provide a composite carrying a large amount of inorganic porous coordination polymer which is scarcely eliminated and has sufficient hardness, and a production method of the same, and to provide a composite carrying a large amount of metal organic framework (MOF) which is scarcely eliminated and has sufficient hardness, and a production method of the same.SOLUTION: A composite which is a composite including cellulose and an inorganic porous coordination polymer and in which a carrying ratio of the inorganic porous coordination polymer after ultrasonic cleaning operation of the composite is 4-60 wt.%, and a production method of the composite are disclosed. A composite which is a composite including cellulose and a metal organic framework and in which a carrying ratio of the metal organic framework after ultrasonic cleaning operation of the composite is 4-60 wt.%, and a production method of the composite are disclosed.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite of cellulose and an inorganic porous coordination polymer, and a method for producing the same. [Background technology]

[0002] Cellulose has the molecular formula (C 6 H 10 O 5 ) n It is a natural polymer in which many β-glucose molecules are polymerized in a linear chain through glycosidic bonds. Unlike synthetic polymers made from petroleum, cellulose is produced naturally and is also biodegradable, making it an environmentally friendly material. Cellulose also has various characteristics that synthetic polymers do not have. Specific examples of these characteristics include: (i) it is relatively chemically stable and does not dissolve easily in various solvents, (ii) it is heat-resistant and does not decompose or melt even at relatively high temperatures, (iii) it is hydrophilic as well as oleophilic, (iv) it produces little harmful substances when burned, (v) it can be molded into various shapes by dissolving it in special solvents, (vi) it can be given functions by chemical reactions using the hydroxyl groups, (vii) it is less toxic to the human body, and (viii) it does not interact easily with substances such as proteins.

[0003] Moreover, cellulose that has been dissolved and regenerated is called regenerated cellulose, and not only can it be molded into any shape, but also can have voids, which are microporous structures, inside the structure. Taking advantage of their characteristics, natural cellulose and regenerated cellulose are used in a variety of forms and for a variety of purposes, such as various fibers, various nonwoven fabrics, packaging films, excipients, artificial kidneys, filters, and cell culture substrates. Furthermore, in recent years, cellulose nanofibers have been studied. Furthermore, in the wake of the microplastics issue, biodegradable cellulose has once again attracted attention as an old yet new material, and new uses are expected.

[0004] Porous Coordination Polymer (PCP) is a general term for compounds that have a framework structure in which metal ions and ligands are crosslinked, and have pores in the structure. PCPs in which a framework structure is formed by crosslinking metal ions with organic ligands are generally called metal organic frameworks (MOFs). PCPs that are not included in MOFs, i.e., compounds that are composed only of metal ions and ligands with very simple structures (e.g., oxide ions, sulfide ions, fluoride ions, chloride ions, bromide ions, iodide ions, cyanide ions, cyanate ions, thiocyanide ions, etc.), and compounds that do not have organic ligands coordinated to metal ions in the framework structure, are referred to as inorganic PCPs in this specification. Examples of inorganic PCPs include Prussian Blue (hereinafter referred to as PB), which is composed of iron and cyanide ions, and porous crystalline solids composed of polyoxometalates, which are anionic clusters composed of metal ions and oxide ions, and any cation (e.g., metal ions, macrocations, alkylammonium ions, etc.).

[0005] PB, also known as Prussian blue, has been used as a pigment since ancient times, but in recent years it has also attracted attention as a functional material. Its applications have been proposed, including adsorbents that utilize the pores in the crystal structure of PB, electrochromic materials that utilize the change in the valence of iron ions, and electrode materials. A series of compounds in which the iron (II) ions and iron (III) ions that compose PB are replaced with other metal species are called Prussian Blue Analogues (hereinafter referred to as PBA). PBA, like PB, has pores in its crystal structure, and various physical properties such as color tone, stability, crystal structure, and electronic structure can be adjusted by combining metal species, so it has attracted attention as a functional material like PB.

[0006] In addition to the method of synthesizing PBA by mixing a solution containing dissolved metal ions and a solution containing dissolved hexacyanometallate at room temperature and pressure, there are other methods of synthesizing PBA under high temperature and pressure, synthesizing the solution while applying microwaves or ultrasound, and synthesizing the raw materials in a solid state and applying mechanical shock with a ball mill. In all cases, PBA is obtained in a powder state, and after synthesis, it is washed and recovered by membrane filtration or centrifugation. When inorganic PCP other than PBA is produced, it is basically obtained in a powder state. However, depending on the application, handling problems may occur in the powder state. To solve this problem, a method has been proposed in which inorganic PCP is supported on some kind of support and used as a composite.

[0007] The following Patent Document 1 reports a method for obtaining a composite knit of cellulose and HKUST-1 by using a cotton knit as a support and an acrylic ester resin as a binder to support HKUST-1 powder, which is a type of metal-organic framework.

[0008] The following Patent Document 2 reports a method for obtaining a composite in which PB is fixed to the surface of cellulose by using cellulose fibers as a support and mixing a first liquid, a solution of potassium hexacyanoferrate (II) aqueous solution and cellulose fibers, with a second liquid, an aqueous solution of iron (III) chloride.

[0009] The following Patent Document 3 reports a method for obtaining a composite of cellulose and PBA by using a regenerated cellulose nonwoven fabric as a support, impregnating the support with a dispersion of a previously synthesized PBA, and drying the support.

[0010] The following Patent Document 4 reports a method for obtaining a composite of cellulose and MOF-90, a type of metal-organic framework, by using oxidized cellulose nanofibers as a support, treating the support with an aqueous zinc nitrate solution to introduce zinc ions as counter ions for the carboxyl groups, washing the support, and then adding a DMF solution of 2-imidazolecarbaldehyde.

[0011] The following Patent Document 5 reports a method of dispersing zinc oxide fine particles in a DMAc solution in which polyethersulfone is dissolved, applying the solution with an applicator, and drying by heating to prepare a film in which zinc oxide particles are dispersed, and then adding a DMAc solution of 2-methylimidazole to obtain a composite of ZIF-8, a type of metal-organic framework, and polyethersulfone. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] JP 2019-88499 A [Patent Document 2] JP 2019-49063 A [Patent Document 3] Patent No. 6345774 [Patent Document 4] Patent No. 6566463 [Patent Document 5] Special Publication No. 2019-523701 Summary of the Invention [Problem to be solved by the invention]

[0013] When inorganic PCP is used as a composite supported on a support, it is required that the inorganic PCP is not easily detached, that the pores of the inorganic PCP are not damaged, etc. Furthermore, when inorganic PCP is used for storage or separation, it is desirable to be able to support a large amount of inorganic PCP. In addition, although it depends on the method of using the composite, if the strength of the composite is low, handling becomes poor, so a supporting method that does not reduce the strength of the composite is desirable.

[0014] A composite can be easily obtained by using a binder as in Patent Document 1, but the pores of the inorganic PCP may be blocked by the binder, making it impossible to obtain the original performance, or the inorganic PCP may be desorbed due to deterioration or dissolution of the binder. Patent Document 2 describes that PB is difficult to desorb and has a high ash yield, and describes treatment in the presence of cavitation bubbles, but there is no data on ash yield in the examples, and no example of treatment in the presence of cavitation bubbles is described. In the method of Patent Document 3, the inorganic PCP is simply physically adsorbed on the cellulose surface, so the inorganic PCP is easily desorbed. It is known that the introduction of carboxyl groups by TEMPO-oxidized cellulose described in Patent Document 4 proceeds selectively on the fiber surface and does not react inside. In other words, even with this method, there is a risk that the inorganic PCP will desorb because it is supported on the fiber surface. In addition, since cellulose is oxidized, there is a possibility that the strength will decrease, especially in water, and the applications in which it can be used will be limited. The method of Patent Document 5 allows inorganic PCP to be supported inside the support, so the risk of inorganic PCP detachment may be low. However, as can be seen from the XRD pattern described in Patent Document 5, not all zinc reacts with 2-methylimidazole and is converted into a metal organic framework. In other words, it is difficult to increase the amount of inorganic PCP supported by this method. In addition, this method is limited in the type of support, solvent, and fine particles that can be used as a precursor, and the composite that can be produced is limited.

[0015] As described above, the present inventors have found that the composites obtained by the existing techniques have room for improvement in terms of various performances required for practical use. In view of the above-mentioned state of the art, the problem to be solved by the present invention is to provide a composite that supports a large amount of inorganic PCP, is difficult to detach, and has sufficient strength, and further to provide a composite of various shapes required for the intended use. [Means for solving the problem]

[0016] The present inventors conducted extensive research and experiments to solve the above problems, and unexpectedly discovered that by dissolving cellulose in a solvent containing metal ions and reacting the cellulose with a ligand solution in a state in which the cellulose forms a complex containing metal ions, an inorganic PCP can be synthesized inside the cellulose structure, and a composite can be provided in which the inorganic PCP is supported in a large amount and is difficult to be detached. The present inventors also discovered that this method allows the shape of the composite to be freely changed, allowing the shape of the composite to be provided according to the application, and further surprisingly, that the composite of the present invention has improved strength compared to cellulose alone.

[0017] That is, the present invention is as follows. [1] A composite comprising cellulose and an inorganic porous coordination polymer, the composite having a loading rate of the inorganic porous coordination polymer after an ultrasonic cleaning operation of the composite being 4% by weight to 60% by weight. [2] The ultrasonic cleaning operation is performed by using a dual-frequency ultrasonic cleaner with pure water in a cleaning tank, and performing the following operations: (1) subjecting a glass container containing a solvent that does not dissolve or decompose the inorganic porous coordination polymer and the complex to an ultrasonic cleaner for 5 minutes; (2) replacing the solvent in the glass vessel; The complex according to the above [1], wherein the above procedure is carried out three times in total. [3] The complex according to [1] or [2] above, wherein the inorganic porous coordination polymer is a Prussian blue analogue. [4] The complex according to any one of [1] to [3] above, wherein the cellulose is regenerated cellulose. [5] The composite according to any one of [1] to [4] above, which has any one of the following shapes: staple fiber, long fiber, woven fabric, knitted fabric, nonwoven fabric, film, porous membrane, hollow fiber, particle, or fine particle. [6] The following steps: preparing a cellulose solution in which cellulose is dissolved as a complex containing a metal ion; A step of forming a structure containing cellulose and metal ions from the cellulose solution; and a step of contacting the obtained structure with a solution containing an anion species that reacts with the metal ion to form an inorganic porous coordination polymer, thereby obtaining a composite containing cellulose and an inorganic porous coordination polymer; A method for producing the complex according to any one of the above [1] to [5], [7] The method according to [6] above, wherein the metal ion is any one of copper, zinc, calcium, cadmium, cobalt, nickel, iron, palladium, and magnesium, or any combination thereof. Effect of the Invention

[0018] According to the present invention, a composite can be obtained which has a large amount of inorganic PCP supported, is difficult to detach, is easy to handle, and has any shape, and can be used for various purposes such as storage materials, adsorption materials, separation materials, sustained release materials, and electronic materials. [Brief description of the drawings]

[0019] [Figure 1] 1 shows X-ray diffraction data of the cellulose-PBA(Cu,Fe) composite obtained in Example 5. [Diagram 2] 1 is a SEM photograph of the surface of the cellulose-PBA(Cu,Fe) composite obtained in Example 5. [Diagram 3] 1 is a cross-sectional TEM photograph of the cellulose-PBA(Cu,Fe) composite obtained in Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, an embodiment of the present invention will be described in detail. One embodiment of the present invention is a composite containing cellulose and an inorganic porous coordination polymer, in which the loading rate of the inorganic porous coordination polymer after an ultrasonic cleaning operation of the composite is 4% by weight to 60% by weight.

[0021] In this specification, the term "inorganic porous coordination polymer (inorganic PCP)" refers to a PCP compound that is composed only of metal ions and ligands with a very simple structure (e.g., oxide ions, sulfide ions, fluoride ions, chloride ions, bromide ions, iodide ions, cyanide ions, cyanate ions, thiocyanide ions, etc.), or a compound in which no organic ligands coordinated to metal ions exist in the framework structure. Examples of inorganic PCPs include Prussian blue (PB), which is composed of iron and cyanide ions, and porous crystalline solids composed of polyoxometalates, which are anionic clusters composed of metal ions and oxide ions, and any cation (e.g., metal ions, macrocations, alkylammonium ions, etc.).

[0022] The PBA in the present invention is a cyano-bridged metal complex having a hexacyanometallate ion as a building block, and has the general formula: A x M y [M'(CN) 6 ] z nH 2 It is a compound having a composition represented by O and a structure in which two kinds of metal ions M and M' are crosslinked with a cyanide ion. In the above general formula, A is an alkali metal ion, M is a first metal ion, M' is a second metal ion, and M and M' can be arbitrarily selected from any metal species. Therefore, the PBA of this embodiment can be said to be a metal salt of hexacyanometallic acid. There are various types of PBAs depending on the combination of M and M'. Depending on the valence of M and M' and the synthesis conditions, the PBA may contain an alkali metal ion A derived from the raw material. The PBA of this embodiment can be used alone or in combination of two or more types.

[0023] Various metal ions can be used as the first metal ion constituting the PBA of this embodiment. In order to support the PBA inside the cellulose, it is preferable to use the metal ion used to dissolve the cellulose as the first metal ion. Among them, copper ions, zinc ions, calcium ions, cadmium ions, cobalt ions, nickel ions, iron ions, palladium ions, and magnesium ions are more preferable because they easily dissolve cellulose. Furthermore, copper ions, which give cellulose with voids, are particularly preferable. Only one type of first metal ion may be used, or two or more types may be mixed together.

[0024] The second metal ion constituting the PBA of this embodiment may be any metal species capable of forming a 6-coordinate structure with a cyanide ion, and may be freely selected according to the purpose. Only one type of second metal ion may be used, or two or more types may be mixed and used.

[0025] Various celluloses can be used as the cellulose constituting the composite of this embodiment. Since cellulose has both hydrophilicity and lipophilicity and is insoluble in most common solvents, various solvents can be used when it is used for adsorption separation to separate a target substance from a liquid, or as a catalyst to control a reaction. In addition, since cellulose has a certain degree of heat resistance and does not melt, it can be used in a wide temperature range. Furthermore, when recovering an object to which an inorganic PCP is adsorbed, various solvents can be used, and recovery can be performed in a certain degree of thermal environment. As the cellulose constituting the composite of this embodiment, regenerated cellulose is preferable because it can be molded into any shape as a composite. Among them, regenerated cellulose obtained from a cellulose solution of a metal complex solvent such as cuprammonium, cadoxene, cooxene, nioxene, ginkoxene, EWNN, etc. is more preferable. These regenerated celluloses have a structure in which the obtained cellulose has voids, and as a result, the molecules can easily access the inorganic PCP present inside the composite, making it easy to use for storage, adsorption, separation, and sustained release. Furthermore, cuprammonium method regenerated cellulose is particularly preferable because it is easy to mold and the voids can be controlled.

[0026] In the composite of this embodiment, the inorganic PCP loading rate (ratio) after ultrasonic cleaning is 4% by weight to 60% by weight. If the ratio of inorganic PCP is low, the functions of storage, adsorption, separation, sustained release, etc. may be insufficient. If the ratio exceeds 60% by weight, the toughness of the composite decreases, and depending on the usage, problems in handling may occur. From the viewpoint of performance, the ratio is preferably 10% by weight or more, more preferably 20% by weight or more, and even more preferably 30% by weight or more. From the viewpoint of handling, the ratio is preferably 50% by weight or less, and more preferably 40% by weight or less.

[0027] The ultrasonic cleaning operation is performed using a dual-frequency ultrasonic cleaner with pure water in the cleaning tank. A glass container containing a solvent that does not dissolve or decompose inorganic PCP and the complex is cleaned in the ultrasonic cleaner for five minutes, after which the solvent in the glass container is replaced with fresh solvent and the container is cleaned again. This operation is repeated three times in total. The reason why ultrasonic cleaning is selected as the method for cleaning the composite of this embodiment is that composites of various shapes can be easily cleaned. When performing ultrasonic cleaning, it is necessary to select a solvent in which inorganic PCP does not dissolve or decompose. For example, in the case of PB, pure water can be used as the solvent.

[0028] In the composite of the present embodiment, it is preferable that a certain amount of inorganic PCP is present inside the cellulose. The inorganic PCP present inside is not only less likely to be desorbed, but is also thought to contribute to improving the mechanical properties of the composite.

[0029] The shape of the composite of this embodiment can be arbitrarily selected depending on the application. For example, short fibers, long fibers, woven fabrics, knitted fabrics, nonwoven fabrics, films, porous membranes, hollow fibers, particles, fine particles, etc. can be mentioned. These may be used alone or in combination. They can also be used in combination with other materials or incorporated into some kind of module. Furthermore, the size and shape of the voids can be arbitrarily selected depending on the application. For example, when gas separation is performed, a dense structure can be used to prevent non-selective gas permeation, and when adsorption separation is performed, a sparse structure can be used to increase the specific surface area and improve the adsorption efficiency.

[0030] Another embodiment of the present invention is a method for producing a method for manufacturing a semiconductor device comprising the steps of: preparing a cellulose solution in which cellulose is dissolved as a complex containing a metal ion; A step of forming a structure containing cellulose and metal ions from the cellulose solution; and a step of contacting the obtained structure with a solution containing an anion species that reacts with the metal ion to form an inorganic porous coordination polymer, thereby obtaining a composite containing cellulose and an inorganic porous coordination polymer; The method for producing the composite according to any one of [1] to [5] above includes the steps of: preparing a cellulose solution in which cellulose is dissolved as a complex containing a metal ion; producing a structure containing cellulose and a metal ion from the cellulose solution; and contacting the structure with a solution containing an anion species to synthesize an inorganic PCP inside the cellulose structure. Since the metal ion has already formed a complex with cellulose, the structure obtained by molding from the cellulose solution has metal ions immobilized therein, and when the structure is contacted with a solution containing an anion species, an inorganic PCP can be precipitated inside the cellulose structure. Since one metal ion can be coordinated to one glucose ring constituting cellulose, many metal ions can be immobilized inside the structure, and a large amount of inorganic PCP can be supported. For example, it has been reported that when a cuprammonium solution is used as a solvent, copper ions are coordinated to the hydroxyl groups of C2 and C3. In this method, the structure obtained by molding from the cellulose solution can be treated with a solution containing an anion species in an uncoagulated state to simultaneously coagulate the structure and synthesize the inorganic PCP, or the structure obtained by molding from the cellulose solution can be first coagulated in a poor solvent that does not break the coordination between cellulose and metal ions, and then treated with a solution containing an anion species to synthesize the inorganic PCP. If necessary, a treatment to break the coordination between cellulose and metal ions may be performed after that. Furthermore, when the composite of this embodiment is produced by treating with a solution containing an anion species in a state in which cellulose forms a complex containing a metal ion, the mechanical properties are surprisingly improved compared to cellulose alone. Although the exact principle is unknown, it is possible that the inorganic PCP present inside the cellulose structure contributes as a reinforcing material, that it forms a hydrogen bond with cellulose and contributes as a crosslinking agent, or that the crystalline structure of cellulose itself changes due to the presence of the inorganic PCP during the formation of the structure. The improvement in the mechanical properties of the composite leads to advantages such as improved handleability during actual use.

[0031] In the method of the present embodiment, in terms of increasing the amount of inorganic PCP supported, a method is preferred in which the structure obtained by molding from the cellulose solution is treated with a solution containing an anion species in an uncoagulated state, thereby simultaneously coagulating the structure and synthesizing the inorganic PCP (or its intermediate). On the other hand, in terms of controlling the shape and voids of the cellulose, a method is preferred in which the structure is first coagulated with a poor solvent that does not break the bond between cellulose and metal ions, and then treated with a solution containing an anion species. In addition, the support rate of the inorganic PCP can be adjusted by changing the conditions such as the concentration, temperature, and reaction time of the solution containing an anion species. In addition, for example, when a cuprammonium solution is used as a solvent for cellulose, the pH becomes alkaline due to the presence of ammonia, so that some types of inorganic PCP may not precipitate. In such cases, a method is also preferred in which the structure is coagulated by deammonification with a poor solvent that does not break the bond between cellulose and metal ions, and then treated with a solution containing an anion species. In addition, depending on the type of inorganic PCP, the reaction may be insufficient or an intermediate may be generated just by treating with a solution containing an anion species. In such cases, high pressure treatment, high temperature treatment, treatment with an acidic solution, treatment with an alkaline solution, ultrasonic treatment, microwave treatment, etc. may be carried out as necessary.

[0032] After the inorganic PCP is synthesized inside the cellulose of this embodiment, a washing treatment can be performed as necessary. If unreacted metal ions or anion species remain in the composite, they can be dissolved and washed with a solvent that does not decompose the synthesized inorganic PCP. For example, in the case of a cellulose-PB composite, pure water can be used as the solvent.

[0033] The composite of this embodiment may be dried as necessary, or may be used as it is without drying, or may be used after solvent replacement. When the synthesized inorganic PCP is solvated and has low activity, drying or activation treatment may be required. If it is desired to maintain the voids of the cellulose, it may be dried by solvent replacement or used as it is without drying. EXAMPLES

[0034] First, the evaluation methods used in the following Examples and Comparative Examples will be described. As an example, the evaluation method of the cellulose-PB composite will be described, but the solvent and container used for washing may be selected taking into consideration the solubility of the metal ions and anion species forming the inorganic PCP and the stability of the inorganic PCP.

[0035] <Measurement of inorganic PCP loading rate in the composite> The composite is dried by heating under reduced pressure at 105°C for one day and night, and the bone dry weight of the composite is measured. Next, the composite is immersed in 3 wt% caustic soda in a sealable container for one hour to decompose and elute the inorganic PCP supported on the composite. Next, the composite is removed and immersed in 10 wt% sulfuric acid in another sealable container for one hour to elute the metal ions remaining in the composite. The above immersion process in 3 wt% caustic soda and 10 wt% sulfuric acid is repeated once more. The remaining cellulose structure is collected and washed with pure water. The obtained cellulose structure is dried by heating under reduced pressure at 105°C for one hour, and the bone dry weight of the cellulose structure is measured. The inorganic PCP support rate of the composite is calculated from the measured bone dry weight of the composite and the bone dry weight of the cellulose structure using the following formula: Inorganic PCP loading rate of the composite (%) = {(bone dry weight of the composite - bone dry weight of the cellulose structure) ÷ bone dry weight of the composite} × 100 It is calculated as follows.

[0036] <Washing procedure for the complex> An AS ONE ultrasonic cleaner (ASU-6D, dual frequency switching type) is used as the ultrasonic cleaner, and pure water is placed in the cleaning tank. The complex is then placed in a sealable glass container and cleaned for 5 minutes with the ultrasonic cleaner. After 5 minutes of cleaning, the pure water in the glass container is replaced, and the ultrasonic cleaning process is repeated a total of three times.

[0037] <Measurement of loading rate when inorganic PCP cannot be decomposed> When the inorganic PCP cannot be decomposed, the cellulose is dissolved using a solvent such as NMMO that dissolves cellulose but does not decompose the inorganic PCP, and the bone dry weight of the isolated inorganic PCP is measured. From the measured bone dry weights of the composite and the inorganic PCP, the inorganic PCP loading rate of the composite is calculated using the following formula: Inorganic PCP loading rate of the composite (%) = {(bone-dry weight of inorganic PCP) ÷ bone-dry weight of the composite} × 100 It is calculated as follows.

[0038] <Calculation of inorganic PCP desorption rate before and after cleaning operation> The desorption rate of inorganic PCP before and after the washing operation was calculated from the inorganic PCP loading rate of the composite before and after the washing operation using the following formula: Inorganic PCP desorption rate of the complex (%) = {(support rate before washing - support rate after washing) ÷ support rate before washing} × 100 It is calculated as follows.

[0039] <Example 1: Preparation of cellulose-PB composite film> Cotton linters were dissolved in EWNN by a known method to prepare a stock solution with a cellulose concentration of 4.0 wt%, iron concentration of 1.5 wt%, tartaric acid concentration of 12.9 wt%, and sodium hydroxide concentration of 18.7 wt%. The stock solution was cast on an 8 cm square glass substrate with an applicator to a film thickness of 300 μm. Next, 50 ml of pure water was placed in a 10 cm square stainless steel container with a lid, and the glass substrate was immersed for 10 minutes while heating to 40 °C to cause coagulation. Next, 50 ml of 2.5 wt% potassium hexacyanoferrate (II) aqueous solution was placed in a 10 cm square stainless steel container with a lid, and the glass substrate was immersed for 30 minutes while heating to 40 °C to cause a reaction between the iron (III) ions that form a complex with the hydroxyl groups of cellulose and the hexacyanoferrate (II) ions. Next, 50 ml of 2 wt% sulfuric acid was placed in a 10 cm square stainless steel container with a lid, and the glass substrate was immersed for 10 minutes. The film after immersion in sulfuric acid was a deep blue color characteristic of PB. The film was then peeled off from the glass substrate and placed in a 10 cm square stainless steel container with a lid together with 50 ml of pure water. The film was rinsed by pinching it with tweezers to wash off the PB adhering to the surface, and then left to stand in the pure water for 5 minutes to wash off the sulfuric acid remaining in the film. This series of washing procedures was repeated until no coloring due to PB detachment in the pure water was observed. The washed film was sandwiched between a 5 cm square stainless steel mold and dried under reduced pressure at 50°C for one day and night while suppressing drying shrinkage, to obtain a dried film. When analyzed using an X-ray diffraction measurement device (Rigaku's X-ray diffraction device "Mini FlexII"), both cellulose and PB peaks were confirmed. From the above results, it was confirmed that a cellulose-PB composite film was obtained.

[0040] <Example 2: Preparation of cellulose-PB composite film> A cellulose-PB composite film was prepared in the same manner as in Example 1, except that the coagulation liquid used was a 50% by weight aqueous acetone solution instead of pure water.

[0041] <Example 3: Preparation of cellulose-PB composite film> A cellulose-PB composite film was prepared in the same manner as in Example 1, except that the coagulation step in pure water was omitted and the cast film was immersed in a 2.5 wt% aqueous solution of potassium hexacyanoferrate(II) to simultaneously carry out coagulation and reaction.

[0042] <Preparation of regenerated cellulose film> Cotton linters were dissolved in a cuprammonium solution by a known method to prepare a cellulose cuprammonium solution with a cellulose concentration of 10% by weight, an ammonia concentration of 7% by weight, and a copper concentration of 3.6% by weight. The solution was cast on an 8 cm square glass substrate with a film thickness of 300 μm using an applicator. The glass substrate was immersed in 50 ml of pure water for 10 minutes while heating to 40°C in a 10 cm square stainless steel container with a lid, and solidified. The glass substrate was immersed in 50 ml of 2% sulfuric acid for 10 minutes in a 10 cm square stainless steel container with a lid, and decoppered. The decoppered film was taken out, placed in a 10 cm square stainless steel container with a lid, and immersed in 50 ml of pure water for 5 minutes to wash off the sulfuric acid. The immersion in pure water was repeated a total of three times until the sulfuric acid was completely washed off. The washed film was sandwiched between a 5 cm square stainless steel mold, and dried under reduced pressure at 50°C for one day and night while suppressing drying shrinkage, to obtain a regenerated cellulose film.

[0043] <Comparative Example 1: Preparation of cellulose-PB composite film by post-processing> Referring to Patent Document 2, 50 ml of 2.5 wt% potassium hexacyanoferrate (II) aqueous solution and a regenerated cellulose film were mixed in a sealable glass container and left to stand for 10 minutes. Then, 50 ml of 2.0 wt% iron chloride (III) aqueous solution was added, the container was closed, and left to stand for 10 minutes. The obtained film was washed with pure water as in Example 1, sandwiched between an 8 cm square stainless steel mold, and dried under reduced pressure at 50°C for one day and night while suppressing drying shrinkage, to obtain a dried film. The obtained film was a deep blue color characteristic of PB.

[0044] <Comparative Example 2: Preparation of cellulose-PB composite film by post-processing> With reference to Patent Document 3, potassium hexacyanoferrate (II) and iron chloride (III) were reacted in advance to synthesize PB particles, which were then dispersed in pure water and applied to a regenerated cellulose film and dried, to obtain a dried film in the same manner as in Comparative Example 1. The obtained film had a deep blue color characteristic of PB.

[0045] <Evaluation of physical properties of cellulose-PB composite film> The PB loading rate was measured using a portion of the cellulose-PB composite films obtained in Examples 1 to 3 and Comparative Examples 1 and 2. A washing operation was then performed, and the PB loading rate after washing was measured, and the PB desorption rate before and after the washing operation was calculated. The results are shown in Tables 1 and 2 below.

[0046] [Table 1]

[0047] [Table 2]

[0048] As is clear from Table 1, the composites obtained in Examples 1 to 3 had a high PB loading rate, and furthermore, PB was less likely to be removed by washing. On the other hand, as is clear from Table 2, the composites obtained by methods other than the present embodiment had a low PB loading rate, and were more likely to be removed by washing. In addition, when each film and a regenerated cellulose film not carrying PB were pulled to check the handling, the films obtained in Comparative Examples 1 and 2 were broken with the same force as the regenerated cellulose film. In contrast, the films obtained in Examples 1 to 3 were less likely to be broken than the regenerated cellulose film.

[0049] Example 4: NH of Cellulose-PB Composite Film in Liquid 4 + Ion adsorption performance evaluation> Ammonium chloride was dissolved in pure water and NH 4 +An aqueous solution with a concentration of 200 ppm was prepared. Then, 0.5 g (bone dry weight) of the cellulose-PB composite film prepared in Example 1 was immersed in 50 mL of the aqueous solution and allowed to stand at room temperature for 24 hours to remove NH 4 + The NH in the remaining liquid after removing the film was 4 + The concentration was measured by the formalin method described in JIS K 1441. The evaluation results are shown in Table 3 below.

[0050] [Table 3]

[0051] As is clear from Table 3, the cellulose-PB composite film obtained in Example 1 had a NH 4 + The adsorption performance was shown.

[0052] <Example 5: Preparation of cellulose-PBA(Cu,Fe) composite film> A cellulose-PBA(Cu,Fe) composite film was prepared in the same manner as in Example 1, except that a cellulose cuprammonium solution was used as the cellulose solution. The film was green when reacted with an aqueous solution of potassium hexacyanoferrate (II), but when treated with 2% sulfuric acid, it turned into the reddish brown color characteristic of PBA(Cu,Fe). When analyzed using an X-ray analyzer, peaks for both cellulose and PBA(Cu,Fe) were confirmed, as shown in Figure 1. Next, the surface and cross section of the film obtained in Example 5 were observed by SEM and TEM, respectively. Photographs of the respective films are shown in Figures 2 and 3.

[0053] <Example 6: Preparation of cellulose-PBA(Cu,Fe) composite film> A cellulose-PBA(Cu,Fe) composite film was prepared in the same manner as in Example 5, except that the coagulation liquid used was a 2% by weight aqueous solution of caustic soda instead of pure water, and the film was immersed in 50 ml of pure water for 5 minutes after coagulation, and the operation of replacing the film with pure water was repeated three times. The obtained film had a reddish brown color characteristic of PBA(Cu,Fe). When analyzed using an X-ray analyzer, peaks for both cellulose and PBA(Cu,Fe) were confirmed.

[0054] <Example 7: Preparation of cellulose-PBA(Cu,Fe) composite film> A cellulose-PBA(Cu,Fe) composite film was prepared in the same manner as in Example 3, except that a cellulose cuprammonium solution was used as the cellulose solution. The obtained film had a reddish brown color characteristic of PBA(Cu,Fe). When analyzed using an X-ray analyzer, peaks of both cellulose and PBA(Cu,Fe) were confirmed.

[0055] <Example 8: Preparation of cellulose-PBA(Zn,Fe) composite film> A cellulose-PBA(Zn,Fe) composite film was prepared in the same manner as in Example 1, except that a zincoxene solution was used as the solution for dissolving cotton linters, and the cellulose concentration was 7% by weight, the zinc concentration was 4.5% by weight, and the ethylenediamine concentration was 13.5% by weight. The obtained film was white. When analyzed using an X-ray analyzer, peaks for both cellulose and PBA(Zn,Fe) were confirmed.

[0056] <Example 9: Preparation of cellulose-PBA(Cu,Co) composite film> A cellulose-PBA(Cu,Co) composite film was prepared in the same manner as in Example 1, except that a cellulose cuprammonium solution was used as the cellulose solution and a 2.5 wt% aqueous potassium hexacyanocobaltate(III) solution was used as the reaction liquid after coagulation. When analyzed using an X-ray analyzer, peaks for both cellulose and PBA(Cu,Co) were confirmed.

[0057] <Evaluation of physical properties of cellulose-PBA composite film> The physical properties of the cellulose-PBA composite films obtained in Examples 5 to 9 were evaluated, and the results are shown in Table 4 below.

[0058] [Table 4]

[0059] As is clear from Table 4, in the methods of Examples 5 to 9, by changing the combination of metal ions and hexacyanometallate ions in the cellulose solution, various PBA-supported composites could be obtained.

[0060] <Example 10: Preparation of cellulose-PBA(Cu,Fe) composite long fibers> A cellulose cuprammonium solution was poured into pure water and tension-spun in a conventional manner to obtain gel-like long fibers containing cellulose and copper. Next, 50 ml of 2.5 wt% potassium ferricyanide (II) aqueous solution was placed in a 10 cm square stainless steel container with a lid, and the long fibers were immersed for 30 minutes while heating to 40°C to react the copper ions complexed with the hydroxyl groups of the cellulose with the ferricyanide (II) ions. Next, the long fibers were taken out and placed in a 10 cm square stainless steel container with a lid containing 50 ml of 2 wt% sulfuric acid and immersed for 10 minutes. Next, the long fibers were taken out and placed in a 10 cm square stainless steel container with a lid together with 50 ml of pure water and shaken to wash off the PBA (Cu, Fe) attached to the surface, and then left to stand in pure water for 5 minutes to wash off the unreacted ferricyanide (II) ions and sulfuric acid. This series of washing operations was repeated until no coloring due to the release of PBA (Cu, Fe) was observed in the pure water. The resulting washed long fibers were wound around a 5 cm square stainless steel frame and dried under reduced pressure at 50° C. for one day and night while suppressing drying shrinkage, to obtain dried long fibers.

[0061] <Example 11: Preparation of cellulose-PBA(Cu,Fe) composite knit> The continuous fibers obtained in Example 10 were tubularly knitted on a tubular knitting machine to obtain a cellulose-PBA(Cu,Fe) composite knitted fabric.

[0062] <Example 12: Preparation of cellulose-PBA(Cu,Fe) composite hollow fiber> A cellulose-PBA(Cu,Fe) composite hollow fiber was prepared in the same manner as in Example 6, except that a double concentric spinneret was used to spin a hollow fiber using a cellulose cuprammonium solution as the outer liquid and a 2 wt% caustic soda solution as the inner liquid, and the fiber was discharged into a bath of a 2 wt% caustic soda solution. The obtained hollow fiber (2.5 g) was immersed in 50 ml of pure water for 5 minutes and the pure water was replaced three times.

[0063] <Example 13: Preparation of cellulose-PBA(Cu,Fe) composite long fiber nonwoven fabric> A cellulose-PBA(Cu,Fe) composite long fiber nonwoven fabric was prepared in the same manner as in Example 10, except that wet spunbond spinning of a cellulose cuprammonium solution was carried out by a conventionally known method.

[0064] <Example 14: Preparation of cellulose-PBA(Cu,Fe) composite particles> The cellulose cuprammonium solution was diluted to adjust the viscosity to 60 mPa·s, and spray-dried by a conventional method to prepare particles containing cellulose and copper. Next, 50 ml of 2.5 wt% potassium ferricyanide (II) aqueous solution was placed in a 10 cm square stainless steel container with a lid, and 0.5 g of the particles was immersed for 30 minutes while heating to 40°C to react the copper ions complexed with the hydroxyl groups of the cellulose with the ferricyanide (II) ions. After the reaction, the particles were collected by centrifugation, and placed in a 10 cm square stainless steel container with a lid containing 50 ml of 2 wt% sulfuric acid and immersed for 10 minutes. Next, the particles were collected by centrifugation, placed in a centrifuge tube together with 50 ml of pure water, and shaken to wash off the PBA (Cu,Fe) attached to the surface, and then left to stand in pure water for 5 minutes to wash off the unreacted ferricyanide (II) ions and sulfuric acid. This series of washing procedures was repeated until no coloring due to the release of PBA (Cu,Fe) was observed in the pure water. The washed particles were collected by centrifugation and dried under reduced pressure at 50°C for one day and night to obtain dried particles.

[0065] <Example 15: Preparation of cellulose-PBA(Cu,Fe) composite particles> Cellulose-PBA(Cu,Fe) composite microparticles were prepared in the same manner as in Example 14, except that the cellulose cuprammonium solution was diluted to adjust the cellulose concentration to 0.37% by weight, the cellulose cuprammonium solution was coagulated with a 27% by weight aqueous acetone solution, and 2.5 g of particles recovered by centrifugation after coagulation was immersed in 50 mL of pure water for 10 minutes to replace the pure water.

[0066] <Evaluation of physical properties of cellulose-PBA(Cu,Fe) composites with different shapes> The composites obtained in Examples 10 to 15 all had a reddish brown color specific to PBA(Cu,Fe). The physical properties were evaluated in the same manner as for the composite film. The results are shown in Table 5 below.

[0067] [Table 5]

[0068] As is clear from Table 5, the complex obtained by the method of this embodiment could be prepared into any shape.

[0069] <Comparative Example 3: Preparation of cellulose-PB composite long fiber by post-processing> Using the regenerated cellulose long fibers obtained from the cellulose cuprammonium solution, cellulose-PB composite long fibers were prepared in the same manner as in Comparative Example 1. The PB loading rate of the obtained composite long fibers was 8.7% by weight, and the PB loading rate after ultrasonic cleaning was 3.4% by weight.

[0070] <Example 16: Preparation of cellulose-PBA(Cu,Fe) composite film> A cellulose-PBA(Cu,Fe) composite film was prepared in the same manner as in Example 5, except that the composition of the cellulose cuprammonium solution was changed to a cellulose concentration of 10 wt%, an ammonia concentration of 8 wt%, and a copper concentration of 4.3 wt%.

[0071] <Example 17: Preparation of cellulose-PBA(Cu,Fe) composite film> A cellulose-PBA(Cu,Fe) composite film was prepared in the same manner as in Example 5, except that the potassium hexacyanoferrate (II) concentration in the reaction solution was 1.0% by weight.

[0072] <Example 18: Preparation of cellulose-PBA(Cu,Fe) composite film> A cellulose-PBA(Cu,Fe) composite film was prepared in the same manner as in Example 5, except that the potassium hexacyanoferrate (II) concentration in the reaction solution was 0.5% by weight.

[0073] <Example 19: Preparation of cellulose-PBA(Cu,Fe) composite film> A cellulose-PBA(Cu,Fe) composite film was prepared in the same manner as in Example 5, except that the potassium hexacyanoferrate (II) concentration in the reaction solution was 0.1% by weight.

[0074] <Example 20: Preparation of cellulose-PBA(Cu,Fe) composite film> A cellulose-PBA(Cu,Fe) composite film was prepared in the same manner as in Example 5, except that after casting the film, it was air-dried instead of coagulating with pure water.

[0075] <Evaluation of physical properties of cellulose-PBA(Cu,Fe) composite film> The composites obtained in Examples 16 to 20 all had a reddish brown color characteristic of PBA(Cu,Fe). Table 6 below shows the evaluation results of the physical properties of the composite films.

[0076] [Table 6]

[0077] As is clear from Table 6, in Examples 16 to 20, the amount of PBA supported could be controlled by adjusting the metal ion concentration in the cellulose solution, the hexacyanometallate ion concentration in the reaction solution, the coagulation method, and the like. [Industrial Applicability]

[0078] The composite of the present invention can be used for gas storage such as hydrogen storage, gas separation for the purpose of suppressing carbon dioxide emissions, etc., filters for removing chemical impurities from gases and liquids, additives that serve as reaction fields for polymer synthesis, etc., catalysts for controlling reactions, adsorption separation for separating target substances from gases or liquids, recovery of valuable materials from liquids, dialysis membranes for removing waste products from blood, sustained-release agents for sustained release of substances trapped in voids, interior materials for buildings and automobiles having deodorizing, humidity-regulating and antibacterial properties, ion-conductive materials, electrodes and separators for secondary batteries, electrochromic materials, and the like.

Claims

1. A composite comprising cellulose and an inorganic porous coordination polymer, the composite having a loading rate of the inorganic porous coordination polymer of 4% by weight to 60% by weight after an ultrasonic cleaning operation.

2. The ultrasonic cleaning operation is performed using a dual-frequency switching ultrasonic cleaner containing pure water in a cleaning tank, and the following operations are performed: (1) subjecting a glass container containing the complex and a solvent that does not dissolve or decompose the inorganic porous coordination polymer to an ultrasonic cleaner for 5 minutes; (2) replacing the solvent in the glass container; The complex according to claim 1, wherein the above procedure is carried out three times in total.

3. The complex according to claim 1 or 2, wherein the inorganic porous coordination polymer is a Prussian blue analogue.

4. The composite according to any one of claims 1 to 3, wherein the cellulose is regenerated cellulose.

5. The composite according to any one of claims 1 to 4, which has any one of the following shapes: short fiber, long fiber, woven fabric, knitted fabric, nonwoven fabric, film, porous membrane, hollow fiber, particles, and fine particles.

6. The following steps: preparing a cellulose solution in which cellulose is dissolved as a complex containing a metal ion; A step of forming a structure containing cellulose and metal ions from the cellulose solution; and a step of contacting the obtained structure with a solution containing an anion species that reacts with the metal ion to form an inorganic porous coordination polymer, thereby obtaining a composite containing cellulose and an inorganic porous coordination polymer; A method for producing the complex according to any one of claims 1 to 5, comprising:

7. 7. The method of claim 6, wherein the metal ion is any one of copper, zinc, calcium, cadmium, cobalt, nickel, iron, palladium, magnesium, or any combination thereof.

Citation Information

Patent Citations

  • Electrically conductive cellulosic fiber

    JP1987097911A

  • Adaptor for fixing electrical connector

    JP1988045774A

  • Cellulose based conducting fiber or film and manufacture thereof

    JP1988048705A

  • Sterilizable regenerated cellulosic fiber

    JP1988249776A

  • Composite fiber of metal ferrocyanide compound and fiber and method for producing the same

    JP2019049063A